Sustainable development and landscape valorization - Cuevas, Karla Gómez (2022)
The landscape is a tourist attraction of international character that reflects customs, traditions and knowledge with respect to the man-nature relationship; therefore, it contains an endless number of meanings and interpretations. However, there are elements inherent to this activity that threaten its integrity and compromise its value. The objective of this paper is to examine the relationship between sustainable development and the valorization of the landscape within a tourism context. For this purpose, a cabinet analysis is chosen, gathering scientific documents for their analysis and interpretation. The results show that sustainability is an indispensable requirement and a decisive factor for landscape valorization. Likewise, landscape valorization serves as a useful instrument for sustainable development by trying to find a plan that allows preserving such meanings and value. In conclusion, the relationship is reciprocal; they function as flexible drivers to detonate natural and economic benefits, contributing to social welfare and favoring tourism.